Early Miocene mammals of Beaulieu (Bouches-du-Rhône, France), comparison with Wintershof-West and the problem of the MN3/MN4 boundary - Aguilar, Jean-Pierre; Antoine, Pierre-Olivier; Crochet, Jean-Yves; López-martínez, Nieves; Métais, Grégoire; Michaux, Jacques; Welcomme, Jean-Loup (Coloquios de Paleontología, 2003)
Beaulieu’s biochronological level is defined by four localities, contemporaneous of the volcanism dated -17,5 ± 0,3 My., among which two of them are in correlation with marine deposits dated in biozones N6 + N7. The microfauna (rodents and lagomorphs) indicates a high level in the time interval named the «cricetid vacuum « (zones B of AGUILAR (1982) or MN 3 (DE BRUIJN et al., 1992), probably younger than Wintershof-West, while the macrofauna is indicating their sub-contemporaneity. The radiometric age and the normal polarity of the basalt allow to discuss about the MN3 / MN4 boundary.